Evaluation of additional points in the 24-2C visual field test in pre-perimetric glaucoma - Gökhan Çelik; Tuncay Karaçocuk; Furkan Çiftci (Photodiagnosis and Photodynamic Therapy)
Background: Early detection and prevention of glaucoma progression are critical. However, studies of early visual field (VF) changes, particularly those using the 24-2C VF test, are limited. Evaluation of additional points in 2C may help identify glaucoma at an early stage, enabling timely intervention. Pre-perimetric glaucoma (PPG) is characterised by structural damage without noticeable VF loss in standard tests. Assessments of changes in retinal nerve fibre layer (RNFL) and macular ganglion cell complex (mGCC) thickness are valuable, but exploring how these structural changes are related to functional deficits is crucial. Objective: This study focused on the average of the additional points in the 24-2C test to understand their correlation with structural measures in the PPG. Material and method: This study included 59 patients with PPG and 36 healthy individuals. All the patients underwent peripapillary and macular optical coherence tomography (OCT) (Nidek RS-3000 Advance; Nidek, Japan). RNFL thickness was evaluated using peripapillary OCT, and mGCC thickness was evaluated using the macular OCT glaucoma module. The mean deviation (MD), pattern standard deviation (PSD), visual field index (VFI), and average of additional points in the 2C (AAP-2C) were evaluated using the 24-2C SITA Faster VF Humphrey Field Analyser III Model 850 (HFAIII; Zeiss Meditec, Dublin, CA, USA). The relationship between structural and functional parameters was statistically evaluated. Results: The PPG group showed significantly lower RNFL and mGCC thickness values than the healthy group. The MD, PSD, and VFI did not differ significantly between the groups. For AAP-2C, the PPG group showed significantly lower sensitivity than healthy individuals. A statistically significant positive correlation between was observed between AAP-2C and mGCC thickness (p = 0.003, r = 0.385). However, the RNFL and mGCC thickness values showed no statistically significant correlations with the MD, PSD, and VFI. Conclusion: Although no glaucomatous change was observed in the VF in patients with PPG, these patients showed reduced sensitivity of the additional points. The reduced sensitivity of the additional points in the 24-2C VF test may reflect early macular functional alterations that correlate with structural damage during the pre-perimetric period.